Hubungan Antara Dukungan Sosial dengan Kualitas Hidup pada Orang Dengan HIV dan AIDS (ODHA) Di Yayasan Spirit Paramacitta - Diatmi, Komang; Fridari, I Gusti Ayu Diah (Jurnal Psikologi Udayana; Vol 1 No 2 (2014)DO - 10.24843/JPU.2014.v01.i02.p14, 2014)
The people who were infected by HIV would be very susceptible from illness, cause by the damage of the immune system. In the daily life, those people must be able to cope complex problems. Not only coping the physiological problems, but also coping the stigma and discrimination which can increase the psychological problems of people with HIV and AIDS. These complex problems will affect to the decrease of quality of life. One of the factor which has important role in quality of life is social support. Based on the background above, this research is aimed to determine the correlation between social support and quality of life on people with HIV and AIDS at Spirit Paramacitta Foundation.   This research was a quantitatif research with correlation method. The sample of this research were 76 people which were choosed by cluster sampling technique. Two kind of scales, there were social support scale and quality of life scale were used to gathered the data. The data were analyzed by correlation product moment with SPSS version 17.0. The research finding showed that the value of correlation coefficient (r) was 0,666 with the significance (p) 0,000. It meant that there was a positif correlation between social support and quality of life on people with HIV and AIDS at Spirit Paramacitta Foundation.   Keywords : social support, quality of life, people with HIV and AIDS